Influence of rainfall on tropical coastal artisanal fisheries: a case study of Northern Mozambique - Hoguane,Antonio Mubango (2012)
The artisanal catch contributed about 87% of the overall annual marine fish production in Mozambique, estimated to 115,000 -140,000 tons, as per fish statistics of the period 2000 and 2004. The availability of most of the coastal marine fisheries depends on a number of factors among which the freshwater input into the coastal waters, either though the rivers or coastal rainfall drainage, as it provides nutrients into the coastal waters that stimulate the primary production. This would enhance the survival and growth of coastal fish species, most of which nurse and breed in estuaries and mangrove swamps. The effect of the freshwater input into the coastal zones through the rainfall 1995-2008 on the landing of artisanal catches 1998-2008 in the northern Mozambique (15o- 17o S) was analysed. The results showed that the artisanal annual total catch were significantly correlated to the coastal rainfall lagged two years, with r= 0.7862 and p=0.004. The two-year lag matches the longevity of Engraulididae, Clupeidae and Leiognathidae, and the maturity age of Carangidea, the top four dominant fish families. This result emphasises the role of freshwater in productivity of coastal waters and in the survival and growth rate of the fish population during the earlier stage of their life cycle. The findings in this work may contribute to predict the fish production, and hence improve the management measures of the artisanal fisheries, through setting sustainable fishing quotas. Further, our results contribute to improve our understanding of the climate influence on artisanal fisheries, and so to provide insights of their vulnerability and adaptive capacity to the climate change.